2009
DOI: 10.1016/j.febslet.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine mediates transforming growth factor‐beta 1 release in kidney glomeruli of diabetic rats

Abstract: a b s t r a c tUp regulation of the transforming growth factor-beta 1 (TGF-b1) axis has been recognized as a pathogenic event for progression of glomerulosclerosis in diabetic nephropathy. We demonstrate that glomeruli isolated from diabetic rats accumulate up to sixfold more extracellular adenosine than normal rats. Both decreased nucleoside uptake activity by the equilibrative nucleoside transporter 1 and increased AMP hydrolysis contribute to raise extracellular adenosine. Ex vivo assays indicate that activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 36 publications
(56 reference statements)
3
53
0
Order By: Relevance
“…This effect could be linked to a decreased activity of ENT1 measured in isolated diabetic glomeruli. 22 Similar to our finding, ENT1 activity was found to be decreased in human endothelial cells isolated from gestational diabetes pregnancy 43 or in cells exposed to high glucose concentrations. 44,45 This decreased activity of ENT1 elicits adenosine signaling by ARs as previously described, using inhibitors of ENT1 activity or in ENT1 À / À mice.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This effect could be linked to a decreased activity of ENT1 measured in isolated diabetic glomeruli. 22 Similar to our finding, ENT1 activity was found to be decreased in human endothelial cells isolated from gestational diabetes pregnancy 43 or in cells exposed to high glucose concentrations. 44,45 This decreased activity of ENT1 elicits adenosine signaling by ARs as previously described, using inhibitors of ENT1 activity or in ENT1 À / À mice.…”
Section: Discussionsupporting
confidence: 79%
“…33 Therefore, currently strategies for DN therapy may need to involve interception of both the TGFb and the VEGF signaling pathways. In this way, the A 2B AR antagonist could be a valuable tool because it was demonstrated that it is able to block the increased release of TGF-b from diabetic glomeruli in vitro 22 and the myofibroblast transdifferentiation of masangial cells in vivo, as reported in this work. Similarly, interception of VEGF induction was a remarkable feature.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations